Kajian Intertekstualitas dalam Karya Sastra Indonesia Kontemporer: Intertextuality Studies in Contemporary Indonesian Literary Works - Era Octafiona (ITScience (Information Technology and Science), 2024)
Contemporary Indonesian literature shows development through intertextuality, namely the influence and adaptation of old works in a modern context. This study explores how contemporary writers use intertextuality to create new meanings and convey social and cultural criticism. This study uses a literature study method with a qualitative approach. The research process involves the selection and in-depth analysis of literary works published in the last two decades, identifying intertextual elements such as quotations, allusions, and parodies. Data are analyzed to identify dominant intertextual patterns, and how these elements function in social, cultural, and political contexts. A descriptive-analytical approach is used to present the findings systematically. The study shows that intertextuality in contemporary Indonesian literature not only enriches the narrative but also functions as a tool for social and philosophical criticism. The use of references from classical and religious texts, as well as the integration of local and cultural values, provide additional depth to modern narratives. Contemporary writers utilize intertextuality to create a dialogue between the past and the present, as well as to critique current social and political conditions. Intertextuality plays an important role in contemporary Indonesian literary works, enriching the meaning of narratives and providing tools for social criticism and philosophical reflection. This study provides new insights into the use of intertextuality in the development of modern literature.